An analysis of the factors affecting the partcipation of youth in public policy formulation in Zimbabwe : the case of Mutare Urban from 2010-2016. - Mwaruta, Tatenda (Midlands State University, 2020)
This study is designed to analyse the factors causing the youth not to participate in public policy formulation in Zimbabwe using the case study being Mutare Urban from the year 2010-2016. Policy formulation is a vital stage in the public policy realm and the way the policy is made determines the levels of its success. Therefore the lack of youth participation in the formulation stage of the public policy results in the failure to effectively implement of the policy as well. A review of literature was conducted to determine the existing knowledge gap concerning youth participation in public policy formulation. The study used the qualitative technique in the solicitation and presentation of data in order to achieve the objectives of this study. Data was collected using questionnaire, in-depth interviews, observations and document analysis. Based on the findings, it was concluded that the reason behind the youth passive stance in public policy formulation is a result of the government lack of will to involve the youth in public policy formulation. Thematic and content data analysis methods were also adopted in the study of data analysis. Ethical considerations were also observed by the researcher in the study. The study concluded that it is the government’s full commitment to ensure that the youth participate in public policy formulation in Zimbabwe that is when the youth participation will increase in public policy formulation hence she proffered recommendations that are aimed at improving the participation of youth in public policy formulation such as engaging of the youth by the responsible authorities at all times and avoid at all-time not to politicise the policy formulation in community consultative engagements. This study recommends that the government should develop strategies to curb the challenges faced by the youth in trying to be part and parcel of the implementation of community development projects and also have their voices heard.